Expenditure Patterns of Singaporean Tourists in Malaysia - Shuib, Ahmad; Bulan, Dora (Universiti Putra Malaysia Press, 1996)
The patterns of expenditure on major tourist products by Singaporean tourists are analysed. The total household expenditure of the tourists is highly significant in influencing expenditure on transport, food, accommodation, recreational services and souvenirs. The elasticities of expenditure for the tourist products are 0.84 for food items, 0.63 for transport, 0.79 for accommodation, 1.32 for recreational services and 1.49 for souvenirs. Based on the expenditure coefficient, food, transport and accommodation are classified as necessities, while services and souvenirs tend to be considered as luxuries by tourists.